STRATEGI KEAKURATAN KODE DIAGNOSIS BERDASARKAN METODE SWOT - HARJANTI -; Nandani Kusuma Ningtyas (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Based on secondary data it can be seen that the average inaccuracy of the diagnosis code is 34.51%. The causes of inaccuracies of diagnostic codes include officers not using volume 1, the error of block determination, no review of completeness of supporting information. The purpose of this research is to determine the accuracy of diagnosis code based on SWOT method. Type of study of literature study. Secondary data source. Collecting data by collecting research literature on the causes of inaccuracies of diagnostic codes. Analysis of SWOT space matrix data. The result of the research is the SO strategy is to send the coding officer to join the training, using icd-10 latest version. WO strategy is a learning task for employees with graduates, recruitment of employees to reduce the workload of employees. ST strategy is a mistake in making reporting, implementation of health insurance system (JKN), inaccuracy in decision making. The WT strategy is to evaluate the reporting results, coding in accordance with WHO rules. The recommended strategy conclusion is SO strategy by sending Medical Record officer to attend training